Likhaan Philippine Innovation Center - Pascua, Bethany Farrah Y. (College of Architecture, University of the Philippines Diliman, 2019)
This research proposes a feasible and suitable architectural design for a Philippine Innovation Center. Numerous studies have pointed out the key role of research, development, and innovation (RDI) initiatives in fostering economic development. In response to lack of an institutionalized mechanism across different (RDI) efforts in the country, the Philippine Innovation Center provides a space that supervises, integrates, and coordinates these efforts that ultimately showcases the integration of innovation and architecture to realize the country's economic and development goals.